West Nile Fever Virus Infection in Horses in São Paulo State, Brazil - Siqueira, Renata Farinelli de; Hansen, Viviane Soares; Martins, Maria de Fátima Monteiro; Leal, Marta Lizandra do Rego; Bondan, Eduardo Fernandes (Acta Scientiae Veterinariae, 2022)
Background: The West Nile virus (WNV) antibodies were reported in Brazil in the serum samples taken from horses and birds in the Midwest region and Paraíba state in 2008 and 2013, respectively. In 2014, the first human case was confirmed in a rural worker in the state of Piauí and, in 2018, the virus was isolated from the central nervous system of a horse with nervous symptoms in the state of Espírito Santo. The virus is a member of the Flaviviridae family of the genus Flavivirus (neurotropic), infecting several mammalian species, with humans and horses being the most susceptible. Approximately 35% of horses develop clinical signs, thus they are considered the best sentinels for this disease. The aim of this case report is to describe the first confirmed cases of West Nile Fever (WNF) in two horses in the state of São Paulo. Cases: Two horses with neurological symptoms were treated at the Veterinary Hospital of Cruzeiro do Sul University (São Paulo, SP), in 2019. Both horses came from neighboring regions that have a large Atlantic Forest preservation area and are also routes for migratory birds, known to be competent hosts for transmitting the West Nile Fever virus, such as the swallow, the falcon and the hawk. The first one had symptoms, such as weakness and sporadic seizures; however, after recovering, it was hospitalized a few days later due to kidney failure and laminitis. The second one showed incoordination, pelvic limb weakness, and was walking in circles, evolving to seizures. Both animals were euthanized, and their central nervous system samples and total blood samples were tested for rabies, herpes virus, and WNV; the first 2 tests showed negative results. Ribonucleic acids (RNA) were extracted from erythrocytes using the polymerase chain reaction (PCR) technique in-house. The WNV-specific reverse transcription-polymerase chain reaction amplification products were obtained using the nested PCR-multiplex PCR combination. Discussion: Since the 1940s, several WNF outbreaks have been reported around the world (Africa, Europe, Asia and Middle East). In the 2000s, the USA had the most amount of WNF cases reported; cases started being reported in Central and South America in the following years. The virus was identified for the first time in Brazil in 2014. Since then, our country is a route for migratory birds, with many states still having forests, several arboviruses are found such as WNF, which could become a public health problem. Both horses in the present study showed neurological signs and the horse that recovered had renal failure. Such signs are inconclusive, however, similar to those that occur in humans infected by the virus in its neurotropic form. The emergence of new diseases is an important aspect of public health. The literature is vast regarding the description of the pathogenesis, clinical signs, diagnosis, viral persistence and sequelae of WNF in humans, however, it is scarce regarding the viral persistence and sequelae of the disease in horses. Future studies are needed to understand the post-infection period in horses, as they are the most sensitive animals along with humans to this virus. Here, we report the first confirmed cases of WNF in the city of São Paulo to bring awareness about considering this disease while diagnosing horses with nervous system disorders. Keywords: encephalitis, horses, flavivirus, mosquito. Título: Infecção pelo vírus da Febre do Nilo Ocidental em equinos no Estado de São Paulo Descritores: encefalite, equinos, flavivírus, mosquito.